Literature Review: The Advantages of Bonding Attachment to Prevent Baby Blues in Post Partum Moms - Resky Salsasisca Sephianti; Herry Susanto; Sri Wahyuni; Nopi Nur Khasanah (Indonesian Journal of Global Health Research, 2025)
The postpartum period is a transitional period that is physically and emotionally challenging for a mother. One of the emotional disorders that often appear during this period is baby blues, which is a feeling of sadness, anxiety, and irritability that usually occurs in the first week after childbirth. This study aims to identify and analyze the benefits of bounding attachment in preventing baby blues in postpartum mothers through a systematic review of scientific literature. This study used a Systematic Literature Review design with reference to the PRISMA guidelines. Article searches were conducted through two main databases, namely PubMed and Google Scholar, with a publication range between 2020 and 2025. The search strategy was organized based on the PICO approach, using keywords such as "bounding attachment", "baby blues", and "postpartum mother". Of the 320 articles found, a selection process based on inclusion and exclusion criteria was carried out to obtain 10 articles that were analyzed in depth. The analysis showed that bounding attachment has significant benefits in reducing the risk of baby blues. Bounding attachment is a simple but effective intervention in preventing emotional disorders in postpartum mothers, especially baby blues.